On the satellite remote measurements of vertical temperatude profile of the Antarctic atmosphere - Tanaka, Shinya; Yoshino, Takeo; Yamanouchi, Takashi; Kawaguchi, Sadao (国立極地研究所, 1982)
A receiving system for High Resolution Picture Transmission (HRPT) data of the TIROS-N/NOAA series meteorological satellites has been installed at Syowa Station, Antarctica. One of the TIROS Operational Vertical Sounder (TOVS)-HIRS/2-data were analyzed and the vertical temperature profiles were derived. The statistical method and the minimum information method were used to retrieve the temperature, and the average errors were estimated as 3℃ and 6℃ respectively compared to the radiosonde observations made at Syowa Station. departmental bulletin paper